Respostas

2014-08-13T23:26:39-03:00
Resolva essa equação??

a) 2 - 3 ( 2 m + 1 ) = 7 m 
   
   2 - 6m - 3          = 7m
   2- 3 - 6m = 7m
     - 1 - 6m = 7m
  - 6m - 7m = + 1
  - 13m = 1
x = - 1/13 





b) X\5 + 2 = 3 ( X - 9 ) + 1 
     x           
   -----  + 2  = 3(x-9) + 1
    5
  
    x
  ------  + 2  = 3x - 27 + 1
    5


 x     + 10   = 15x - 135 + 5  fração com igualdade desprezamos o denominador
---------------------------------------
                5

 
x + 10 = 15x - 135 + 5
x + 10 = 15x  - 130
x - 15x =  - 130  - 10
- 14x = - 140
x = - 140/-14
x = + 140/14
x = 10